The Interplay Between Vitamin D Deficiency, Iron Status, and Anemia Risk in Moroccan Women of Reproductive Age: A Cross-Sectional Analysis - Noura Zouine; Ilham Lhilali; Lode Godderis; Adil El Midaoui; Samir El Jaafari; Younes Filali-Zegzouti (Epidemiologia)
Background: Vitamin D and iron deficiencies are prevalent among Moroccan women of reproductive age (WRA). Research suggests that Vitamin D deficiency (VDD) may impair iron bioavailability, potentially leading to iron deficiency (ID) and anemia. Objectives: This study investigates associations between vitamin D status, iron levels, and anemia risk in WRA, aged 18–49, from Meknes, Morocco. Methods: A cross-sectional study was conducted among 463 participants, measuring serum 25(OH)D, blood count parameters, iron, ferritin, C-reactive protein, and creatinine. Lifestyle factors, including dietary intake, sun exposure, and physical activity, were assessed through validated questionnaires, and anthropometric data were collected. Linear and logistic regression models analyzed associations, while ROC analysis evaluated VDD’s predictive accuracy for ID and anemia. Results: VDD (25(OH)D < 20 ng/mL) was significantly associated with reduced hemoglobin, hematocrit, red blood cells, and ferritin (all p < 0.01), indicating vitamin D’s role in erythropoiesis and iron storage. Multivariate logistic regression showed that VDD increased the risk of anemia (OR: 7.17, 95% CI: 3.19–19.28, p < 0.001), ID (OR: 2.20, 95% CI: 1.32–3.77, p = 0.007), and IDA (OR: 4.10, 95% CI: 1.73–12.08, p = 0.004). Dietary iron intake was inadequate, showing minimal protective effects against anemia and ID (β(SE): −0.08(0.03), p = 0.030 and β(SE): −0.05(0.02), p = 0.037). Conclusions: VDD is a significant risk factor for impaired iron status and anemia in Moroccan WRA, highlighting the need for targeted nutritional interventions and further research.